‘Pretty devastating’: exploring horse owner and veterinarian lived experiences of the equine Hendra virus - White, Jennifer; Thompson, Kirrilly; van den Berg, Debra; O’Neill, Genevieve; Mendez, Diana H.; Talwar, Joanne; Degeling, Chris; Forsythe, Rebecca; Durrheim, David N. (Frontiers in Veterinary Science, 2025)
IntroductionWith more than 60% of emerging infectious diseases being zoonotic, we apply a One Health lens that connects human, animal, and environmental dimensions of the response to a Hendra virus (HeV) event. One Health promotes collaboration among health professionals, veterinarians, environmental scientists, and policymakers to strengthen health infrastructure and improve responses to complex health threats. HeV is an uncommon high-consequence and potentially fatal zoonotic disease endemic to parts of Australia. Previous research has largely focused on the uptake of preparedness measures by veterinarians and horse owners and less is known about the emotional and experiential factors that may influence their behaviours.MethodsThis study applied Interpretative Phenomenological Analysis to examine how horse owners and veterinarians experience, interpret, and act on HeV risk within a One Health frame of reference. Our aim was to characterise lived experiences at the human–animal–system interface and identify actionable, cross-sector recommendations. We conducted semi-structured interviews with eight horse owners and five veterinarians in a regional area of northern New South Wales, Australia.ResultsResults identified four superordinate themes from the horse owners and two overarching themes from veterinarians. Findings highlight the emotional complexity of recognising and responding to HeV, including grief responses, and implications for future public health strategies. The need for comprehensive support structures underscored by public health liaison with a trusted general practitioner and dedicated access to mental health practitioners experienced in emergency and crisis contexts emerged as an important finding. A need for clear guidance for managing uncertain or deteriorating equine health was identified.ConclusionThese findings demonstrate how qualitative social science, applied within a One Health framework, can inform targeted messaging, policy considerations and cross-sector responses to emerging zoonoses, including HeV.